1994
DOI: 10.1121/1.409169
|View full text |Cite
|
Sign up to set email alerts
|

Within-category discrimination of musical chords: Perceptual magnet or anchor?

Abstract: Recent speech research has demonstrated that the presence of prototypes may be reflected in the internal structure of speech categories. Some speech results have found lower discrimination in a vowel P context compared to a NP context, suggesting that a prototype may function as a perceptual magnet, effectively decreasing perceptual distance, and thus, discriminability, between stimuli. The current study examines the function of prototypes in a musical category; another natural, but nonspeech, category. Protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…However, recent evidence indicates that the perceptual magnet effect found for speech might not always be found for other categories. In particular, Acker, Pastore, and Hall (1995) have reported that for musical chords, discrimination is actually better, rather than worse, in the region of the category prototype. This suggests that category prototypes might function somewhat differently across domains, and that this difference might interact with the type of task used to assess the underlying structure (see also Krumhansl, 1978Krumhansl, , 1979Tversky, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence indicates that the perceptual magnet effect found for speech might not always be found for other categories. In particular, Acker, Pastore, and Hall (1995) have reported that for musical chords, discrimination is actually better, rather than worse, in the region of the category prototype. This suggests that category prototypes might function somewhat differently across domains, and that this difference might interact with the type of task used to assess the underlying structure (see also Krumhansl, 1978Krumhansl, , 1979Tversky, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it is possible to experiment with any of the possible image pair combinations described above, including paired easy/difficult images (ie, eN/dA and dN/eA); there is evidence that both difficult and easy training can be effective. [24][25][26] However, categorical perception theory intuitively suggests that training on paired images drawn from the same diagnostic category (ie, eN/dN or eA/dA) would not be very effective, simply because observers might require exposure to objects from different diagnostic categories if they are to learn to distinguish them. In purely practical terms, we would like to know which of the paired image combinations enhances diagnostic performance most effectively.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment by Acker et al (1995) that was described in the introduction is clearly relevant to the present outcomes. (Their work was unknown to us at the time we conducted the present experiments, but their results suggest that the stimuli do not have to be as complex as were ours for a discrimination advantage to be observed for CE stimuli in this context.)…”
Section: Resultsmentioning
confidence: 99%
“…One set of relevant demonstrations comes from research on the perception of musical intervals. Acker, Pastore, and Hall (1995) measured auditory frequency discrimination using stimuli consisting of three tones presented simultaneously. One or two of those tones were changed slightly in frequency from the values in a standard stimulus, and the participants indicated in which observation interval that change occurred.…”
mentioning
confidence: 99%